The rhetorical structure and persuasive principles used in Malaysian smartphone web advertisements / Thenmalar Chandran - Thenmalar , Chandran (2020)
The aim of this study is to identify the rhetorical structure used in Malaysian smartphone web advertisements. This study also aims to identify how the principles of persuasions are realised in the Malaysian smartphone web advertisements. The five websites used for the purpose of this research were selected based on a Google Search which indicated the top five most popular and accessed websites. The first five websites that were shown and selected were www.11street.com.my, www.directd.com.my, www.satugadget.com.my, www.ipmart.com.my and www.lazada.com.my and 11street.com.my. The five smartphone models and brands were selected based on the latest International Data Corporation (IDC) Quarterly Mobile Phone Tracker which was recorded in the year 2016. The moves found in the web advertisements were identified using Bhatia’s framework for advertisements (2004) while the principles of persuasions used in the web advertisements were identified using Cialdini’s principles of persuasion (2007). The findings of this research showed that the moves in the advertisements not only serve the communicative purpose of informing and introducing the details of the smartphones to the readers but also persuade them to buy the product. It was also found out that the smartphone web advertisements have some moves that were not specified in Bhatia’s framework for advertisements (2004). In short, this study is able to add on some literature in the field of genre analysis and also enrich the framework proposed by Bhatia (2004) for a specific product.